Project “Schule für alle” as a mentoring programme in university teacher education: Professionalization processes of student teachers in different practical university phases - Kottmann, Brigitte; Pieper, Catania (Hungarian Educational Research Journal)
In the mentoring programme project “Schule für alle” (“School for all”) at the University of Bielefeld in North Rhine-Westphalia, university students of primary or special education support a child who is in a situation of crisis for more than one year. In addition, the university students receive ongoing, systematic university support (cf. Kottmann, 2007, p. 32; Kottmann, 2014, p. 380). The accompanying research by “Schule für alle” focuses on the professionalization processes of student teachers during practical phases at universities; accordingly, control groups were included on a pro rata basis. In the pre-post design, all students completed a questionnaire (cf. Pieper, Kottmann & Miller, 2018, p. 294), the evaluation of which shows few changes in the professional perception of competence. Students of the mentoring programme also regularly reflected on their practical experience. Based on the objective hermeneutics it was discovered that the conception of the project supports the process of perceiving, acknowledging and becoming more sensitive in regard to heterogeneous realities in life (cf. Pieper & Kottmann 2019b, p. 312) and that students can consciously perceive and reflect their own normative expectations (cf. Pieper & Kottmann 2019a, p. 79). The article primarily presents the results of the pre-post survey in detail and adds insights into the qualitative evaluation processes. In the conclusion, the potential of the project and mentoring programmes in general, specifically for teacher training students, is described.
Keywords: professionalization of teacher training students; practical university phases; teacher training at universities; men-toring programmes